Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Usaha Kecil Menengah Klaster di Desa Celuk - Septiarini, Septiarini; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 4, April 2016 (pp.385 - 429), 2016)
It’s necessary to increase the productivity of SMEs because it will increase the production and generation of income. The main objective of  this research is  to analyze the research that the employer has knowledge on particularly on the productivity of SME clusters, to analyze the differences in productivity among SMEs and to receive government help compared to those who do not receive any government assistance,  and to analyze the effect of investments in partially on the productivity of SME clusters. The data used in this study are primary and secondary data. The sampling technique in this research is to collect information from multiple government, private and corporate SMEs. While the data analysed will be collected an outcome and a result will be shown in illustration. (Graphs, Pie Chart, Figures). Based on the analysis, it can be concluded that: Education Entrepreneur’s have a positive and significant effect on the Peroduktivitas SME clusters, SME clusters who receive government assistance have greater productivity compared to SME clusters that do not receive government assistance, Investments are both positive and will have a significant effect on the productivity of SME clusters
Keywords: SME clusters; Entrepreneur Education; Government Aid; Investment; Productivity.